Inconspicuous breeding coloration to conceal eggs during mouthbrooding in male cardinalfish - Hikaru Ishihara; Shinji Kanda (iScience)
Summary: Animals exhibit colorations optimal for their niche, which hides their existence from other organisms. In Apogoninae fishes, the father broods their egg inside their mouth. Since the color of eggs is different from parental fish, it can disrupt the optimal camouflage coloration of parental fish if the lower jaw is transparent. Here, we identified male- and breeding season-specific whitish coloration consisting of iridophores in the lower jaw. Artificial implantation of eggs inside the mouth of females and males showed that iridophores in the lower jaws concealed the conspicuous coloration of eggs only in males. In addition, it was revealed that iridophore development in the lower jaw is induced by androgen through the Alkal-Ltk pathway. These results suggest that androgen-dependent breeding colorations in males, which have been considered to attract females, may serve the opposite function, “inconspicuous breeding coloration” in these species.